Ecological associations of the coastal marsh periwinkle snail Littoraria irrorata: field and laboratory evidence of vegetation habitat preferences - Klinges,David H.; Martin,Charles W.; Roberts,Brian J. (PeerJ, 2025)
Coastal salt marshes serve as the margin between terrestrial and marine biomes, provide a variety of important services, and are dynamic ecosystems characterized by keystone species that shape trophic networks. In coastal salt marshes of the Atlantic and Gulf Coasts of the United States, marsh periwinkle snails (Littoraria irrorata) exhibit high abundance and form critical trophic pathways as important herbivores and detritivores. Specifically, snails forage on Spartina alterniflora and associated fungal growth, for which L. irrorata may act as a top-down control on plant growth. Yet, L. irrorata occupies other salt marsh plants, suggesting its habitat niche may be broader than previously reported. Here, we documented snail densities and size distributions in a Louisiana (USA) salt marsh composed of multiple marsh graminoids and report the results of behavioral choice experiments designed to test snail habitat preferences as a potential mechanism underlying their field distribution. We observed higher snail densities on S. alterniflora stalks (283 snails m−2) than other plant species, however, snails were highly abundant on S. patens (116 snails m−2), Juncus roemerianus (95 snails m−2), and Distichlis spicata (57 snails m−2) with densities comparable or higher on all species than reported on S. alterniflora in other studies along the U.S. Atlantic and Gulf coasts. Snails found on S. alterniflora and J. roemerianus, both plants with tall and rigid stalks, were also larger than snails found on other plant species. In species preference experiments, snails preferred S. alterniflora over S. patens and D. spicata, but no clear preferences were observed between S. alterniflora and J. roemerianus, nor between any combinations of S. patens, D. spicata, and J. roemerianus. Finally, we found that snails preferred senescing and dead S. alterniflora tissue over fresh S. alterniflora. Interpreting these results in tandem, this study suggests L. irrorata snails have consistent patterns of field distributions that match their habitat preferences, and future studies should test potential processes driving snail habitat selection, such as dietary habits and predator refugia (i.e., climbing sturdy stalks to avoid aquatic predators). Considering the abundance and trophic role of L. irrorata in coastal salt marshes, snail behavior may be a key modulator for salt marsh trophic networks.
Keywords: Salt marsh; Gulf Coast; Spartina alterniflora; Distichlis spicata; Juncus roemerianus; Spartina patens; Experiment; Snail density